The macroeconomic effects of shadow banking panics - Johannes Poeschl (Danmarks Nationalbank, 2020)
We study the effects of shadow banking panics in a macroeconomic model with a rich financial system, including deposit-financed retail banks and wholesale-financed shadow banks. The model can quantitatively match the dynamics of key variables around the US financial crisis. Wholesale funding market interventions akin to those implemented by the Federal Reserve in 2008 reduced the fall in output by about half a percentage point. Generally, central bank interventions reduce output volatility and the likelihood of banking panics.
Keywords: E44; G24; G28; 330; Financial Institutions; Financial Stability; Interconnectedness; Monetary Policy